Dissecting human trophoblast cell transcriptional heterogeneity in preeclampsia using single‐cell RNA sequencing. Issue 8 (2nd July 2021) - Zhang, Tao; Bian, Qianqian; Chen, Yanchun; Wang, Xiaolin; Yu, Shaowei; Liu, Shunhua; Ji, Ping; Li, Ling; Shrestha, Mandakini; Dong, Shujun; Guo, Rong; Zhang, Hong
Abstract: Objective: PE is a pregnancy‐specific syndrome that affects 3%–5% of pregnant women. It often presents as new‐onset hypertension and proteinuria during the third trimester. PE progresses rapidly and may lead to serious complications, including the death of both mother and fetus. In low‐income countries, PE is one of the main causes of maternal and child mortality. While the cause of PE is still debated, clinical and pathological studies suggest that the placenta plays an important role in the pathogenesis of PE. Materials and Methods: In this single‐cell RNA‐sequencing (RNA‐seq) study, the placenta was taken from the designated position after cesarean section. We compared placental cell subsets and their transcriptional heterogeneity between preeclampsia and healthy pregnancies using the single‐cell RNA‐seq technology. A developmental trajectory of human trophoblasts was shown. Results: Gene expression in endoplasmic reticulum signaling pathways in syncytiotrophoblast was upregulated in the PE group. The villi cytotrophoblasts (VCT) and extravillous trophoblasts were mainly involved in immune responses. Conclusion: The placental immune function of patients with PE was altered. Proteasomes, spliceosomes, ribosomes, and mitochondria were abnormally active in the new VCT cell type. Abstract : This information has enriched our understanding of the human placenta and broadened our understanding of the molecular functions of the human placenta in the diseased state. These findings will be helpful in the future discovery of new molecular markers and the discovery of drugs for the treatment of the disease.